A persistent cough as atypical clinical presentation of intrathoracic extramedullary hematopoiesis (EMH) in a female with thalassemia intermedia - Abdulla, Mohammad AJ; Yassin, Mohamed A; Abdelrazek, Mohamed; Mudawi, Deena; Ibrahim, Firyal; Soliman, Dina S; ElOmri, Halima; Nashwan, Abdulqadir J; Fernyhough, Liam Joseph; de Sanctis, Vincenzo; Soliman, Ashraf T (Acta Biomedica Atenei Parmensis, 2018)
Extramedullary hematopoiesis (EMH) is a rare disorder, defined as the appearance of hematopoietic elements outside the bone marrow or peripheral blood. The most common sites of EMH are liver and spleen, but it has been documented in other organs such as the mediastinum, lymph nodes, breast, and central nervous system. EMH occurs as a compensatory mechanism for bone marrow dysfunction in severe thalassemia. We report a case of EMH presenting as a posterior mediastinal mass in a 34-year-old woman with thalassemia intermedia with chronic cough and shortness of breath on exertion. The diagnosis of EMH was confirmed by a CT-guided fine needle biopsy. All symptoms disappeared after surgical removal of the mass.